Academic Procrastination and Perfectionism (Adaptive and Maladaptive) - Amanda, Devina; Siaputra, Ide Bagus; Lasmono, Hari K. (ANIMA Indonesian Psychological Journal, 2012)
This study aims to explain the relationship pattern between academic procrastination and perfectionism (adaptive and maladaptive). The theoretical basis of this study is TMT (Temporal Motivation Theory) which was measured by Task Utility (TU) instrument. A quantitative method approach was applied using Spearman correlation technique. The data obtained was processed with SPSS 16 for Windows. The subjects (N = 518) were psychology students. The results showed the absence of adequate correlations between academic procrastination and the two types of perfectionism (adaptive and maladaptive). The inadequate correlations were affected by two factors which are the existence of a mediator variable and the instrument (PASS-1 and APS-R) used. This study concludes that in adaptive perfectionism, flexibility of perception towards one’s own standard affects the feelings that procrastination is not a problem. On the contrary in maladaptive perfectionism, one’s own rigid standard affect the feelings that procrastination is a problem and should be reduced. Penelitian ini bertujuan untuk menjelaskan pola hubungan prokrastinasi akademik dan perfeksionisme (adaptif dan maladaptif). Dalam penelitian ini landasan teoretik yang digunakan adalah TMT (Temporal Motivation Theory) yang diukur melalui alat ukur Utilitas Tugas (UT). Penelitian ini menggunakan pendekatan kuantitatif dengan teknik korelasi Spearman dan data diproses dengan SPSS 16 for Windows. Subjek penelitian (N = 518) adalah mahasiswa fakultas psikologi. Hasil yang diperoleh menunjukkan tidak adanya korelasi memadai antara prokrastinasi akademik dan dua tipe perfeksionisme (adaptif dan maladaptif). Korelasi yang tidak memadai ini dipengaruhi oleh dua hal yakni adanya variabel eksternal yang berpengaruh (mediator) dan faktor alat ukur (PASS-1 dan APS-R) yang digunakan. Dengan demikian dapat disimpulkan bahwa pada perfeksionisme adaptif, fleksibilitas pandangan terhadap standar yang dimiliki memengaruhi perasaan bahwa prokrastinasi bukanlah sebuah masalah. Sebaliknya, pada perfeksionisme maladaptif kekakuan standar memengaruhi adanya perasaan bahwa prokrastinasi merupakan sebuah masalah yang ingin dikurangi.